2021
DOI: 10.1038/s41377-021-00548-z
|View full text |Cite
|
Sign up to set email alerts
|

Localization-limited exciton oscillator strength in colloidal CdSe nanoplatelets revealed by the optically induced stark effect

Abstract: Abstract2D materials are considered for applications that require strong light-matter interaction because of the apparently giant oscillator strength of the exciton transitions in the absorbance spectrum. Nevertheless, the effective oscillator strengths of these transitions have been scarcely reported, nor is there a consistent interpretation of the obtained values. Here, we analyse the transition dipole moment and the ensuing oscillator strength of the exciton transition in 2D CdSe nanoplatelets by means of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(92 citation statements)
references
References 45 publications
4
88
0
Order By: Relevance
“…Clearly, the reduced confinement in the out-of-plane direction compared to thin nanoplatelets, combined with strong carrier–carrier interactions evidenced by strong band gap renormalization and comparatively fast radiative bimolecular recombination, strongly reduces the excitonic nature of the fundamental excitations in QRs. We did not observe any correlation between the QR’s unique g = 1 topology and the ultrafast phenomena discussed here which could be due to limited rotational symmetry, as observed similarly by Hartmann et al, or carrier localization at room temperature . Overall, CdSe QRs at room temperature behave more as classical quantum wells, providing a unique platform for studying unbound charge carriers in colloidal materials.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Clearly, the reduced confinement in the out-of-plane direction compared to thin nanoplatelets, combined with strong carrier–carrier interactions evidenced by strong band gap renormalization and comparatively fast radiative bimolecular recombination, strongly reduces the excitonic nature of the fundamental excitations in QRs. We did not observe any correlation between the QR’s unique g = 1 topology and the ultrafast phenomena discussed here which could be due to limited rotational symmetry, as observed similarly by Hartmann et al, or carrier localization at room temperature . Overall, CdSe QRs at room temperature behave more as classical quantum wells, providing a unique platform for studying unbound charge carriers in colloidal materials.…”
supporting
confidence: 74%
“…We did not observe any correlation between the QR’s unique g = 1 topology and the ultrafast phenomena discussed here which could be due to limited rotational symmetry, as observed similarly by Hartmann et al, 10 or carrier localization at room temperature. 44 Overall, CdSe QRs at room temperature behave more as classical quantum wells, providing a unique platform for studying unbound charge carriers in colloidal materials.…”
mentioning
confidence: 99%
“…iv) Finally, at low temperatures, the exciton giant oscillator strength connected with the coherent exciton motion in NPLs leads to a further increase of the radiative recombination rate. [ 14 ] In CdSe NPLs, the shortening of the radiative decay time [ 3 , 15 ] and giant oscillator transition strength [ 16 , 17 ] have been reported already, suggesting that all the above‐discussed phenomena could bring the radiative decay time of various NPLs down to the range of tens to a few hundreds of ps.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the ground state exciton has a giant oscillator strength (15–23 Debye) due to the exciton center of mass coherent motion. [ 14 ] Therefore, nanoplatelets are beneficial for studying strong light‐matter coupling in microcavities. Lucas et al.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the ground state exciton has a giant oscillator strength (15-23 Debye) due to the exciton center of mass coherent motion. [14] Therefore, nanoplatelets are beneficial for studying strong light-matter coupling in microcavities. Lucas et al [15] observed the anti-crossing behavior of polariton using CdSe nanoplatelets and a tunable planar microcavity with which the coupling constant was estimated to be 33 meV.…”
Section: Introductionmentioning
confidence: 99%